Association between periodontitis and lung disease - Fabiano Rito Macedo; Eduardo Saba-Chujfi; Silvio Antonio Santos Pereira; Elton Luiz da Costa; José Pereira de Melo Neto (Faculdade São Leopoldo Mandic, 2010)
Objective: To verify the association between periodontal disease and lung disease from an epidemiological, case and control survey, in patients who attended the first aid service of the Adriano Jorge Foundation Hospital, Manaus, Amazonas, Brazil, from June 2006 to February 2007. Methods: The sample consisted of 140 patients, among whom community-acquired pneumonia was present in 60% (n = 70), and chronic obstructive pulmonary disease in 40% (case-group); and 70 patients without respiratory disease (control group), ranging between 19 and 69 years of ages, with a mean age of 41.3, and standard deviation of 13.6 years. The clinical parameters for evaluating periodontal changes were obtained by means of pocket depth, bleeding on probing, plaque index and clinical attachment loss. Results: Both groups showed no significant difference in any of the control variables (p>0.05). The groups showed significant difference only in the plaque index (p <0.05) and the mean was 0.36, standard deviation 0.30 in control group, and in the cases a mean of 0.51, standard deviation 0.35. Conclusion: Periodontal disease showed no significant association with lung disease, both in severity and extension (p> 0.05). Due to the increase in the bacterial plaque index in the oral cavity of patients with respiratory diseases, further studies should be conducted to verify what the relationship between the two diseases is.